Saturn and beyond - Asimov, Isaac, 1920-1992.; Maestro, Giulio (New York : Lothrop, Lee & Shepard, 1979)
Presents a detailed discussion of the four outermost planets in our solar system.
Keywords: Planets; Saturn (Planet) -- Juvenile literature; Uranus (Planet) -- Juvenile literature; Neptune (Planet) -- Juvenile literature; Pluto (Dwarf planet) -- Juvenile literature; Solar system